Syphilitic retinitis in human immunodeficiency virus infection - Margarido, Elisabete (1996)
The authors present a case report of a 25 year old man admitted in the hospital refering bilateral progressive loss of vision. Five years ago, a diagnosis of primary syphilis was made and two years ago he was found to be a HIV positive. Treatment with penicilin was given and the pa tient had an eventful recovery with complete resolution of the retina lesions and recovery of visual acuity. The final diagnosis was syphilitic retinitis.